Factors Affecting the Agricultural Restructuration: A Case of Cham Community in Chau Phu District, An Giang Province, Vietnam - Van Huynh Thanh Pham; Cam Thi Hong Lam; Nghia Ngoc Nguyen (International Journal of Agricultural Sciences, 2020)
The national policy of agricultural restructuring plays a vital role in adapting to climate change's effects and economic development in the Mekong Delta of Vietnam. Unproductive areas have been converted into other crops with higher efficiency. Drawn by the sustainable livelihoods approach, this article explores the current situation and factors challenging the Cham community in implementing the agricultural restructuring. The mixed method included in-depth interviews, focus group discussions, and a questionnaire survey. The results showed that the Xuong Com Vang longan (Dimocarpus longan) variety has occurred in Khanh Hoa commune for a long time as an indigenous fruit tree of this area. In terms of the farming system, the polyculture system combining fruit trees and upland crops brought more income sources than the monoculture system. The asset abilities of the Cham farmers are various from one to the others. Soil and weather conditions are appropriate for planting. But farm size is small, which is one of the difficulties of developing fruit areas. Human and social assets were good since farmers had enough knowledge to manage the gardens, and a close connection existed among the Cham community. It was not a case of the financial status since a lot of money needs to be invested in the starting year. Therefore, the private loan still exists as one of the farmer's choices. For better future development, land management and financial resource should be considered for better agricultural restructuring aims. To increase farmers' incomes, create production chains helping enterprises and farmers work more efficiently for the better life of Cham gardeners in An Giang province in Vietnam.